2021
DOI: 10.1101/2021.02.08.430308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered TGFB1 regulated pathways promote accelerated tendon healing in the superhealer MRL/MpJ mouse

Abstract: To better understand the molecular mechanisms of tendon healing, we investigated the Murphy Roths Large (MRL) mouse, which is considered a model of mammalian tissue regeneration. We show that compared to C57Bl/6J (C57) mice, injured MRL tendons have reduced fibrotic adhesions and cellular proliferation, with accelerated improvements in biomechanical properties. Transcriptional analysis of biological drivers showed positive enrichment of TGFB1 in both C57 and MRL healing tendons. However, only MRL tendons exhib… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…In tendon, latent TGFβ is present in the tendon matrix and is critical for tendon maintenance and regeneration in neonatal mice ( Maeda et al, 2011 ; Kaji et al, 2020 ; Tan et al, 2020 ). However, while it is clear that TGFβ signaling in Scx + tenocytes is critical for tendon healing as well as scar and adhesion formation ( Katzel et al, 2011 ; Goodier et al, 2016 ; Kallenbach et al, 2021 ), it is unclear whether TGFβ released following ECM disruption during injury plays an additional role in immune modulation.…”
Section: Cytokinesmentioning
confidence: 99%
“…In tendon, latent TGFβ is present in the tendon matrix and is critical for tendon maintenance and regeneration in neonatal mice ( Maeda et al, 2011 ; Kaji et al, 2020 ; Tan et al, 2020 ). However, while it is clear that TGFβ signaling in Scx + tenocytes is critical for tendon healing as well as scar and adhesion formation ( Katzel et al, 2011 ; Goodier et al, 2016 ; Kallenbach et al, 2021 ), it is unclear whether TGFβ released following ECM disruption during injury plays an additional role in immune modulation.…”
Section: Cytokinesmentioning
confidence: 99%
“…Previous studies suggested that growth factors could be essential for maintaining the engineered tendon constructs (29,31,32). Transforming growth factor beta (Tgf) is one of the well-known growth factors and is critical for tendon development and tenogenic differentiation in vivo and in vitro (16,31,(36)(37)(38)(39)(40)(41)(42)(43). These previous studies prompted us to use Tgf in the 3D tendon culture.…”
Section: Tgfβ Is Essential For 3d Tendon Culturementioning
confidence: 99%
“…[20][21][22][23][24][25] In particular, our group and others have established that MRL/MpJ mice elicit a scarless healing capacity following acute injury of the patellar, flexor digitorum longus, and supraspinatus tendons compared to those of non-healer C57BL/6 (B6) mice. [20][21][22][23]25,26 We have previously determined using ex vivo organ culture that the local tissue environment rather than systemic contributions (i.e., the immune response) serves as the primary driver of MRL/MpJ (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] In particular, our group and others have established that MRL/MpJ mice elicit a scarless healing capacity following acute injury of the patellar, flexor digitorum longus, and supraspinatus tendons compared to those of non-healer C57BL/6 (B6) mice. [20][21][22][23]25,26 We have previously determined using ex vivo organ culture that the local tissue environment rather than systemic contributions (i.e., the immune response) serves as the primary driver of MRL/MpJ tendon healing 23 . We have also demonstrated that the administration of decellularized MRL/MpJ tendon injured/provisional ECM and cell-derived soluble factors in vitro shifts B6 cells toward a regenerative cellular phenotype 23,27 , which illustrates the promising utility of isolating constituents of the MRL/MpJ tendon biological environment to guide the development of mechanisticallyinformed therapeutics.…”
Section: Introductionmentioning
confidence: 99%